Correction to: Short-term arsenic mobilization, labilization, and microbiological aspects after gasoline and diesel addition in tropical soils (Environmental Geochemistry and Health, (2023), 45, 6, (3541-3554), 10.1007/s10653-022-01425-3) - Luko-Sulato, Karen [UNESP]; Sulato, Everton Tiago [UNESP]; Podsclan, Caroline Barradas [UNESP]; Oliveira, Lucia Maria de Souza de [UNESP]; Yabuki, Lauren Nozomi Marques [UNESP]; Rosolen, Vania [UNESP]; Menegário, Amauri Antonio [UNESP] (Springer Nature, 2023)
In the original publication of the article, the last name of the author “Lauren Nozomi Marques Yabuki” is corrected from “Kabuki” to “Yabuki”. The original article has been corrected.